Adoption of interim measures in the Republic of Uzbekistan - Samarkhojaev, B.B.; Mansurov, A.F. (Bulletin of the Karaganda University “Law Series”, 2024)
Based on the meaning of judicial protection, after a court decision on a dispute, the task of the business process does not end there. In turn, dispute resolution is truly effective only in the case of actual execution and restoration of violated rights; otherwise, a court decision will be a “dead letter”. Thus, it is relevant to give the actual possibility of execution of the final court decision. In other words, the property and non-property assets of the debtor must be accessible and real to the executive power, at the expense of which the judicial act can actually be executed. Thus, modernly developed logistics infrastructure and transport, banking and communication systems, as well as digital opportunities for economic and civil circulation provide many opportunities for the debtor to withdraw his assets from any jurisdiction where the trial on the merits of the dispute is taking place. One of the ways to prevent such transfer of assets outside the country is a court decision. In turn, the final court decision on the merits of the dispute cannot be a prompt means of responding to a violation of this nature. There are circumstances when the applicant or creditor not only does not have time to wait for a final court decision, but also to file a claim. Thus, the most effective means of protection in time-limited disputes by their legal nature are interim measures.